Oriental Clinical Study on a Case of the Sequelae of Spinal SAH - Kyoung hee Lee; Ju hwan Lo; Hyoun-min Youn; Kyung-jeon Jang; Chang-beohm Ahn; Cheol-hong Kim (Korean Pharmacopuncture Institute, 2008)
Objective : Spinal SAH is an unusual disease that occasionally occurs spinal cord injury. This report intended to estimate the effect that taken by using oriental treatment on the patient with the sequelae of spinal SAH. Methods : We have observed this case of patient treated by Dong's acupuncture therapy, pharmacopuncture therapy, Mae-sun therapy and herbal medication, etc. Results : The patient showed improvements in pain, power and sensory function Conclusion : Oriental treatments such as Dong's acupuncture therapy, pharmacopuncture therapy, Mae-sun therapy and herbal medication can be effective for the sequelae of spinal SAH.